Aggressive suicide. Issue 3 (September 2015) - Manning, Jason
Abstract While suicide is often considered deviant, it may also be a kind of social control that expresses and handles moral grievances. The moralistic nature of suicide is especially clear in cases where suicide is used to bring harm against others—that is, cases in which suicide is a kind of interpersonal aggression. The current paper explores aggressive aspects of suicide in a variety of social contexts. Anthropological studies reveal that in many tribal and traditional societies killing oneself is a recognized means of punishing others, who will be subject to supernatural curses or sanctions administered by third parties. Examining a sample of suicide cases in the contemporary U.S., I find that aggressive suicide also occurs in the modern metropolitan world. The chief punitive mechanism in modern aggressive suicide is the infliction of psychological harm, such as guilt. Drawing on Donald Black's paradigm of pure sociology and my previous theoretical work on moralistic suicide, we can explain aggressive suicide with the relational structure of the conflicts in which it occurs. Available data reveal that aggressive suicide is most likely to occur among intimates, and that variation in relational distance predicts the nature and severity of suicide's consequences for the living.